Earth science - Danielson, Eric W. (Macmillan Reference USA, 1989)
Earth Science offers a user-friendly overview of our physical environment with balanced, up-to-date coverage of geology, oceanography, astronomy, and meteorology for the undergraduate student with little background in science. The emphasis is on readability, with clear example-driven explanations.